Experimental and numerical investigations on effect of blade trimming on aerodynamic performance of squirrel cage fan. (1st July 2020) - Wang, Ke; Ju, Yaping; Zhang, Chuhua
Highlight: Blade trimming method is proposed for squirrel cage fan. Trimming is aimed at axial modification of blade inlet. Full trimming is preferable to part trimming in performance improvement. Dimension of inactive zone decreases. Impeller achieves better match with volute tongue. Abstract: The impeller of squirrel cage fan exerts great effects on the internal flow fields and fan aerodynamic performance. On the premise of maintained impeller-volute tongue distance and production cost reduction, this paper proposes a blade trimming method focusing on axial modification of blade inlet in an attempt to improve the impeller flow condition and further the aerodynamic performance of squirrel cage fan, which is divided into blade full trimming and part trimming. Aerodynamic performance tests and numerical simulations are performed to explore the effect of blade trimming on the fan aerodynamic performance and the related flow mechanisms. The results show that the blade trimming with proper trimming parameter enables the fan to achieve higher fan aerodynamic performance in terms of total pressure efficiency and static pressure rise, between which full trimming is preferable to part trimming. With the optimum full trimming of blade, the axial distributions of mass flow at the impeller inlet and outlet become more uniform. The dimension of inactive zone near the front span is decreased. On the blade pressure surface, the forces are reduced with obvious improvement of gradients near the front span and back span. A better match between impeller and volute tongue is achieved as the decreases of reversed flow coefficients at the impeller inlet and outlet and recirculated flow coefficient in the volute. Graphical abstract: Image, graphical abstract